Violencia y justicia durante la posrevolución. El homicidio en el Distrito Federal, 1920-1940 (Tzintzun, Revista de Estudios Históricos, 2016)
This article focuses on the analysis of criminality in the Federal District between 1920 and 1940, based on murder. The paper identifies different forms in which extreme violence manifested itself, in a context marked by the process of the institutionalization of the revolutionary state and by the dynamics of a rapidly growing urban area, with its diverse and complex problems. In our analysis, court records, statistics and newspaper resources have been used.
Keywords: homicide; violence; justice; Federal District; post-revolution